Periodic Solutions for Delayed Malware Mutation Model - Feng, Chunhua (Transactions on Engineering and Computing Sciences, 2025)
This paper investigates the existence of periodic solutions for a malware mutation model with time delays. We extend the result in the literature from a two-delay model to a five-delay model. Using the method of mathematical analysis, the original system has been linearized. The instability of the unique positive equilibrium point and the boundedness of the solutions will force this system to generate a periodic solution. Two sufficient conditions to guarantee the periodic oscillation of the solutions are provided, and computer simulations are given to support the present criteria.